2018
DOI: 10.4025/actascianimsci.v40i1.39663
|View full text |Cite
|
Sign up to set email alerts
|

<b>Growth and meat quality of three free-range chickens and commercial broiler under the same breeding conditions

Abstract: Commercial breed has taken over the Algerian poultry production market which participated in the weakening of the village poultry farming, highly dominant prior to the 1980s. Fortunately, the dietary preferences of consumers, strongly participated in the preservation of the local animal breed diversity. In this context, the aim of this work was to study the growth performances and meat quality of 3 local chicken phenotypes versus commercial broiler chicken in the same breeding conditions in the region of Chlef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…Ao analisar e descrever os aspectos qualitativos que compõem os estudos científicos, considerando o indicador qualidade da carne, verifica-se que os estudos adotam essa temática com abordagens distintas, sendo que Zidane et al (2018), trazem em seus resultados contribuições acerca das melhores linhagens que se adaptaram à região onde o experimento foi realizado, podendo auxiliar na definição de critérios para o estabelecimento de programas de seleção. Por sua vez, Oliveira et al (2015) apresentam os impactos dos diferentes intervalos de jejum alimentar, constatando que ocorre menor rendimento de carcaça no tempo de zero e mais de nove horas de jejum, assim como diferença na capacidade de retenção de água de acordo com o corte analisado (peito, coxa e sobrecoxa).…”
Section: Resultados E Discussõesunclassified
“…Ao analisar e descrever os aspectos qualitativos que compõem os estudos científicos, considerando o indicador qualidade da carne, verifica-se que os estudos adotam essa temática com abordagens distintas, sendo que Zidane et al (2018), trazem em seus resultados contribuições acerca das melhores linhagens que se adaptaram à região onde o experimento foi realizado, podendo auxiliar na definição de critérios para o estabelecimento de programas de seleção. Por sua vez, Oliveira et al (2015) apresentam os impactos dos diferentes intervalos de jejum alimentar, constatando que ocorre menor rendimento de carcaça no tempo de zero e mais de nove horas de jejum, assim como diferença na capacidade de retenção de água de acordo com o corte analisado (peito, coxa e sobrecoxa).…”
Section: Resultados E Discussõesunclassified
“…Chemical analysis (moisture, protein, fat and ash) was performed according to the Association of Official Analytical Chemists (AOAC, 2000). pH was determined using a pH meter (HI 22 11 PH/ORP-instrument HANNA) equipped with an insertion glass electrode (Zidane, Ababou, Metlef, Niar, & Bouderoua, 2018).…”
Section: Measures and Analysismentioning
confidence: 99%
“…Protein content in chicken meat is influenced by several factors, amongst which genotype plays a crucial role. Previous studies have reported the lower protein concentration (22%) in the broiler chicken as compared to the free range chicken (24%) such as the Algerian crested(Zidane et al 2018) and Chinese local chicken "Gushi"(Wang et al 2009), even under similar management conditions Kim et al (2017). reported protein concentration of 20.80 (g/100 g of sample) and 16.93 (g/100 g of sample) for the commercial Cobb broiler breast and thigh, respectively.…”
mentioning
confidence: 94%